A Bird in the House: The Challenge of Being Ecologically Relevant in Captivity - Beaulieu, Michaël (Frontiers in Ecology and Evolution, 2016)
Ecologists have acknowledged the fact that environmental conditions strongly affect life-history strategies in the wild. However, when working in captivity, they appear to overlook these effects. This approach appears precarious, as it likely contributes to increase the inconsistency of results across ecological studies. To illustrate this point, I reviewed here the conditions under which captive zebra finches (Taeniopygia guttata) are kept in studies examining stress parameters that mediate life-history strategies, and compared these conditions to the conditions their wild counterparts experience in their native habitat. I found that captive zebra finches are typically kept under conditions that mostly reflect a paradoxical season in terms of temperature, light and humidity that would never be encountered in the wild. Most importantly, I also found that these conditions are associated with elevated stress levels. This suggests that most studies using captive zebra finches are conducted under stressful conditions, and therefore give a biased and limited view of how birds regulate life-history strategies. This example strongly suggests that we have to rethink our approach when examining ecological questions in captivity, by carefully considering conditions under which animals are kept in view of their current and future ecology.